1988
DOI: 10.1172/jci113758
|View full text |Cite
|
Sign up to set email alerts
|

Impaired insulin-stimulated muscle glycogen synthase activation in vivo in man is related to low fasting glycogen synthase phosphatase activity.

Abstract: Insulin-mediated glycogen synthase activity in skeletal muscle correlates with the rate of insulin-mediated glycogen deposition and is reduced in human subjects with insulin resistance. To assess the role of glycogen synthase phosphatase as a possible mediator of reduced glycogen synthase activity, we studied 30 Southwestern American Indians with a broad range of insulin action in vivo. Percutaneous biopsies of the vastus lateralis muscle were performed before and during a 440-min euglycemic clamp at plasma in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 36 publications
2
31
1
Order By: Relevance
“…When a defect in insulin's ability to activate glycogen synthase has been reported previously, it has usually been accompanied by a corresponding reduced rate of glucose uptake into insulin-sensitive tissues (e.g., 7,[12][13][14][15][16]. This association has lead to the suggestion that a causal relationship exists between insulin-stimulation ofglycogen synthase and glucose uptake (7,13,14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When a defect in insulin's ability to activate glycogen synthase has been reported previously, it has usually been accompanied by a corresponding reduced rate of glucose uptake into insulin-sensitive tissues (e.g., 7,[12][13][14][15][16]. This association has lead to the suggestion that a causal relationship exists between insulin-stimulation ofglycogen synthase and glucose uptake (7,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Although impaired muscle glycogen synthase activity in response to insulin has been well documented in a number of insulin-resistant states (7,(12)(13)(14)(15)(16)(17), little is known about the nature or extent of these defects. In a previous study carried out during steadystate glucose clamp conditions and insulin levels of 300 pmol/ liter, we documented that muscle glycogen synthase activity (expressed as fractional velocity) was reduced by 40% in NIDDM but could be normalized by increasing insulin levels fourfold ( 17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be emphasized that, even if the defect in hexokinase II were corrected, a severe defect in glucose transport most likely would remain (11) and become rate limiting. It also should be pointed out that the observed defect in in vivo muscle glucose phosphorylation observed in the present study could result from a defect distal to hexokinase, i.e., glycogen synthase (15,26,32,48,59,62) or glycolysis/ glucose oxidation (1,22,59), with an increase in glucose 6-phosphate levels (37,40,42,63,64) and product inhibition of hexokinase. Consistent with this scenario, pervious studies have indicated a rate-limiting step for glucose metabolism beyond glucose phosphorylation/glucose 6-phosphate (46,51), and elevated muscle glucose 6-phopshate concentrations have been demonstrated in insulin-resistant rhesus monkeys during insulin infusion (46).…”
Section: Discussionmentioning
confidence: 58%